Hypericum perforatum L. Regulates Glutathione Redox Stress and Normalizes Ggt1/Anpep Signaling to Alleviate OVX-Induced Kidney Dysfunction - Liu, Yan-Ru; Yang, Ning-Juan; Zhao, Meng-Li; Tang, Zhi-Shu; Duan, Jin-Ao; Zhou, Rui; Chen, Lin; Sun, Jing; Song, Zhong-Xing; Hu, Jin-Hang; Shi, Xin-Bo (Frontiers in Pharmacology, 2021)
Menopause and associated renal complications are linked to systemic redox stress, and the causal factors remain unclear. As the role of Hypericum perforatum L. (HPL) in menopause-induced kidney disease therapy is still ambiguous, we aim to explore the effects of HPL on systemic redox stress under ovariectomy (OVX)-induced kidney dysfunction conditions. Here, using combined proteomic and metabolomic approaches, we constructed a multi-scaled ‘HPL-disease-gene-metabolite’ network to generate a therapeutic ‘big picture’ that indicated an important link between glutathione redox stress and kidney impairment. HPL exhibited the potential to maintain cellular redox homeostasis by inhibiting gamma-glutamyltransferase 1 (Ggt1) overexpression, along with promoting the efflux of accumulated toxic amino acids and their metabolites. Moreover, HPL restored alanyl-aminopeptidase (Anpep) expression and metabolite shifts, promoting antioxidative metabolite processing and recovery. These findings provide a comprehensive description of OVX-induced glutathione redox stress at multiple levels and support HPL therapy as an effective modulator in renal tissues to locally influence the glutathione metabolism pathway and subsequent redox homeostasis.